Character Education and Interethnic Interaction for Social Cohesion: A Qualitative Study of Maritime Students in Aceh, Indonesia - Siregar, Muhammad Sapril; Bahrun, Bahrun; ., Husaini; Yunus, Muhammad; Jamil, T. M.; ., Niswanto (Journal of Posthumanism, 2025)
This study aims to explore the role of interethnic social interaction in supporting character education and fostering sustainable social cohesion among maritime students. Methods: A qualitative case study was conducted at a Maritime Polytechnic in Aceh, Indonesia, involving 150 participants, including cadets, lecturers, counselors etc. Data were gathered through in-depth interviews, focus group discussions, and participatory observations. Thematic analysis was employed to identify key patterns of interaction and character formation. Results: The findings indicate that interethnic interactions occurring in shared living spaces, collaborative maritime training, and community-based cultural activities significantly contribute to the development of character values, including empathy, tolerance, leadership, mutual respect, and discipline. Nevertheless, particular challenges such as regional biases and linguistic differences were occasionally found to hinder the development of social cohesion. Conclusion: The study underscores the importance of culturally responsive pedagogical approaches and character-focused curricula in strengthening inclusive citizenship and social harmony in maritime Education.